Coronary functional assessment in non-obstructive coronary artery disease: Present situation and future direction - Zhai, Changlin; Fan, Hongyan; Zhu, Yujuan; Chen, Yunqing; Shen, Liang (Frontiers in Cardiovascular Medicine, 2022)
Non-obstructive coronary artery disease (CAD), which is defined as coronary stenosis less than 50%, has been increasingly recognized as an emerging entity in clinical practice. Vasomotion abnormality and coronary microvascular dysfunction are two major mechanisms contributing to the occur of angina with non-obstructive CAD. Although routine coronary functional assessment is limited due to several disadvantages, comprehensive physiological evaluation is crucial to identify the underlying mechanisms and consequently provide appropriate therapeutic strategies. In this review, we summarized the potential mechanisms involved in ischemia with non-obstructive coronary arteries (INOCA) and myocardial infarction with non-obstructive coronary arteries (MINOCA), the two major form of non-obstructive CAD. Additionally, we reviewed currently available functional assessment indices and their use in non-obstructive CAD. Furthermore, we speculated that novel technique combined anatomic and physiologic parameters might provide more individualized therapeutic choice for patients with non-obstructive CAD.